2019
DOI: 10.1021/acs.jmedchem.9b00352
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Preclinical Efficacy of Novel Nonretinoid Antagonists of Retinol-Binding Protein 4 in the Mouse Model of Hepatic Steatosis

Abstract: Retinol-binding protein 4 (RBP4) serves as a transporter for all-trans-retinol (1) in the blood, and it has been proposed to act as an adipokine. Elevated plasma levels of the protein have been linked *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…BPN-14136 is another non-retinoid compound that disrupts the RBP4 and TTR complex with the potential to treat atrophic age-related macular degeneration and Stargardt disease ( Cioffi et al, 2014 ). Interestingly, a BPN-14136 derivative was able to lower RBP4 and partially prevent high-fat diet induced obesity and hepatic steatosis in mice with adipose tissue-specific transgenic overexpression of human RBP4 described above ( Cioffi et al, 2019 ).…”
Section: Pharmacological Approaches To Lower Circulating Rbp4mentioning
confidence: 97%
See 1 more Smart Citation
“…BPN-14136 is another non-retinoid compound that disrupts the RBP4 and TTR complex with the potential to treat atrophic age-related macular degeneration and Stargardt disease ( Cioffi et al, 2014 ). Interestingly, a BPN-14136 derivative was able to lower RBP4 and partially prevent high-fat diet induced obesity and hepatic steatosis in mice with adipose tissue-specific transgenic overexpression of human RBP4 described above ( Cioffi et al, 2019 ).…”
Section: Pharmacological Approaches To Lower Circulating Rbp4mentioning
confidence: 97%
“…This included palmitic acid, which could be purified from RBP4 in human urine ( Perduca et al, 2018 ). Moreover, palmitic and also linoleic acid, among others, were able to replace 3 H-retinol from human RBP4 ( Cioffi et al, 2019 ). Thus, RBP4 may be a physiologically relevant binding and transport protein for fatty acids.…”
Section: Interaction Of Rbp4 With Non-retinoid Ligandsmentioning
confidence: 99%
“…[ 22 ] After RBP4 was released into blood, it binds to retinol and thyroxine carrier proteins and forms a retinol-RBP4-TTR ternary complex in the form of 1:1:1, which transports retinol to target tissues for specific physiological functions. [ 23 ] Early studies found that RBP4 was associated with fatty liver, glycolipid metabolic diseases such as diabetes mellitus and cardiovascular diseases. [ 4 , 24 ] It was deemed that RBP4 was a fat-derived factor in the blood and was considered as an important target for the treatment of type 2 diabetes mellitus (T2DM), insulin resistance, non-alcoholic fatty liver and visceral obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, another study found fatty acids within the crystal structure of human retinol-free RBP4 isolated from serum, urine, and amniotic fluid [ 97 ]. Several fatty acids showed the capability of 3 H-retinol replacement in the binding pocket of human RBP4, providing another hint to the fatty acid binding and possible transporting function of RBP4 [ 98 ].…”
Section: Rbp4: a Carrier For Non-retinoid Ligands?mentioning
confidence: 99%